Analysis of joint overlap during friction spin welding of plastics. (2020) - Bindal, Tarun; Saxena, Ravindra K.; Pandey, Sunil
Abstract: The joining of plastic parts is gaining its importance because of its use in versatile fields and atmosphere. Thermoplastic parts are widely used due to the adaptability of different joining methods. It is known that most of the parts are joined using the application of heat. The application of adhesive bonding and mechanical fixing is also used in a number of applications. The two axisymmetric parts can easily be joined using friction spin welding technique. In friction spin welding one rotating part interacts with another stationary part to generate heat at the interface under pressure and ultimately joint is formed after cooling. Most of such parts are joined in butt joint configuration. In some of the applications, the shear joint configuration may increase the versatility of the manufactured parts. The joint overlap is an important parameter to be investigated in the shear joint configuration under friction spin welding of the plastic parts. In the present work, the joint overlap is studied during friction spin welding of two axisymmetric thermoplastic parts in the shear joint configuration. The effect of pressure and rotational velocity are studied on the joint overlap. The design of experiments is applied to find the effect of these input parameters on the joint overlap. It is observed that axial pressure is a prominent parameter in comparison to rotational velocity under the investigated range of parameters.